CAND1 promotes PLK4-mediated centriole overduplication and is frequently disrupted in prostate cancer - Korzeniewski, Nina; Hohenfellner, Markus; Duensing, Stefan (Neoplasia, 2012)
Centrosomes play a crucial role in the maintenance of genome stability by orchestrating bipolar mitotic spindle formation. The centrosome normally duplicates precisely once before mitosis in a process that is extensively regulated by protein degradation including SKP1-Cullin 1 (CUL1)-F-box (SCF) E3 ubiquitin ligase activity. The core SCF component CUL1 has recently been found to be required to suppress the formation of supernumerary centrosomes and centrioles, the core-forming units of centrosomes. Here, we identify the CUL1-interacting protein cullin-associated and neddylation-dissociated 1 (CAND1) as a novel centrosomal protein with a role in centriole duplication control. CAND1 was found to synergize with Polo-like kinase 4 (PLK4), a master regulator of centriole biogenesis, in the induction of centriole overduplication. We provide evidence that CAND1 functions in this process by increasing PLK4 protein stability. Furthermore, mutants of CUL1 that lack the ability to interact with CAND1 and are unable to assemble functional E3 ubiquitin ligase complexes were impaired in their ability to restrain aberrant daughter centriole synthesis. To corroborate a role of CAND1 in human carcinogenesis, we analyzed a series of prostate adenocarcinomas and found altered expression of CAND1 on the mRNA or protein level in 52.9% and 40.8%, respectively, of the tumor samples analyzed. These results highlight the role of altered SCF components in cancer in general and encourage further studies to explore the SCF-CAND1 axis for the development of novel predictive biomarkers and therapeutic approaches in prostate cancer.